Exosomal LncRNAs and CircRNAs in lung cancer: Emerging regulators and potential therapeutic targets - Xia Li; Yunbing Wu; Yue Jin (Non-coding RNA Research)
Lung cancer remains one of the most prevalent and lethal malignancies globally, characterized by high incidence and mortality rates among all cancers. The delayed diagnosis of lung cancer at intermediate to advanced stages frequently leads to suboptimal treatment outcomes. To improve the management of this disease, it is imperative to identify new, highly sensitive prognostic and diagnostic biomarkers. Exosomes, extracellular vesicles with a lipid-bilayer structure and a size range of 30–150 nm, are pivotal in intercellular communication and play significant roles in lung cancer progression. Non-coding RNAs (ncRNAs), including long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), are highly prevalent within exosomes and play a crucial role in various pathophysiological processes mediated by these extracellular vesicles. Beyond their established functions in miRNA and protein sequestration, these ncRNAs are involved in regulating translation and interactions within exosomes. Numerous studies have highlighted the importance of exosomal lncRNAs and circRNAs in influencing epithelial-mesenchymal transition (EMT), angiogenesis, proliferation, invasion, migration, and metastasis in lung cancer. Due to their unique functional characteristics, these molecules are promising therapeutic targets and biomarkers for diagnosis and prognosis. This review provides a succinct summary of the formation of exosomal lncRNAs and circRNAs, clarifies their biological roles, and thoroughly explains the mechanisms by which they participate in the progression of lung cancer. Finally, we discuss the potential clinical applications and challenges associated with exosomal lncRNAs and circRNAs in lung cancer.